2007
DOI: 10.1016/j.juro.2007.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Is Ureteroscopy First Line Treatment for Pediatric Stone Disease?

Abstract: Improved ureteroscopic access to stones throughout the pediatric urinary tract and stone-free rates that are comparable to the adult population have led to the adoption of ureteroscopy as first line therapy in children at our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(82 citation statements)
references
References 21 publications
2
68
0
12
Order By: Relevance
“…[13] Barındırdığı bazı komplikasyonlar nedeniyle pediatrik yaş grubunda durum bu kadar net değildir. Bunun yerine ESWL tercihi de doğru bir yaklaşımdır.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…[13] Barındırdığı bazı komplikasyonlar nedeniyle pediatrik yaş grubunda durum bu kadar net değildir. Bunun yerine ESWL tercihi de doğru bir yaklaşımdır.…”
Section: Discussionunclassified
“…Ancak, çocuklarda ESWL'nin anestezi gerektirmesi, genellikle taşın bir kerede kırılamama-sı, ESWL'nin başarısız olduğu vakalarda tedavinin zorunlu olarak ÜRS ile devam etmesi ve üreterin distaline gidildikçe ESWL'nin başarısızlık oranının artması tedavi seçiminde ESWL'nin geri kalmasına yol açmıştır. [13,14] Bizim de 3 hastamızda renal taş, 2 hastamızda ise üreter üst kısmındaki taşlara ESWL öyküsü vardı.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Passive dilatation with preoperative stenting was performed for 38% of the patients, while UAS was used in 43%. Smaldone et al [31] reported that they performed passive and active dilatation in 54% and 70% of the patients respectively, and used UAS in 24% of patients. In this series of 100 patients, SFR was noted as 91%, and 5 perforations were encountered, in which 1 of them needed a re-implantation.…”
Section: Rirs In Pediatric Patientsmentioning
confidence: 99%
“…Beş hastada üreteral perforasyon izlendi. Ama access sheath veya üreter dilatasyonu kullanımıyla ilişkilendirilmedi 12 . Kim ve ark., 167 çocuk hastada yapılan 170 işlemi değerlendirdi.…”
Section: Finansal Destekunclassified